Effect of Topical Epigallocatechin-Gallate on Lipopolysaccharide-induced Pulpal Inflammation in Rat Models - Ismiyatin, Kun; Wahluyo, Soegeng; Purwanto, Djoko Agus; Rahayu, Retno Pudji; Soetojo, Adioro; Mukono, Indri Safitri (Iranian Endodontic Journal, 2018)
Introduction: Pulpal inflammation can be marked by an increase in tumor necrosis factor-α (TNF- α), malondialdehyde (MDA) and calcitonin gene-related peptide (CGRP) level. Epigallocatechin-3-gallate (EGCG) demonstrates the ability to reduce cytokine expression, influence immune receptors, reduce inflammation, neutralize reactive oxygen species (ROS) and to inhibit pain conduction. The present research aimed to determine the anti-inflammatory, antioxidant and pain conduction inhibition of topical EGCG hydrogels in Lipopolysaccharide (LPS)-induced pulpal inflammation in rats. Methods and Materials: A total of 28 male Wistar rats were divided equally into four groups. The negative control group (N) received no treatment, while the positive control group (C) and the other two treatment groups (T1, T2) were induced with LPS for 6 h, followed by the application of topical polyethylene glycol (PEG) hydrogels for C group, 25 ppm EGCG hydrogels for T1 group and 75 ppm EGCG hydrogels for T2 group, before being filled with glass ionomer cement (GIC). After 24 h, PEG and EGCG were reapplied and refilled with GIC for 24 h. The pulp tissue samples were examined by means of immunohistochemistry (IHC) to identify TNF-α, MDA and CGRP expression. All the data obtained was analyzed with one-way analyses of variance (ANOVA) test. Results: The T1 and T2 groups showed a significant decrease in TNF-α and CGRP expression compared to the control group, but there was no significant decrease in MDA in either group (P<0.05). Conclusion: Based on the results of this study, topical application of 75 ppm EGCG hydrogels to the tooth cavities with six hours of pulpal inflammation has the optimal result in reducing the expression of TNF-α and CGRP, but not of MDA. Keywords: Calcitonin Gene-related Peptide; Epigallocatechin-3-Gallate; Malondialdehyde; Pulpal Inflammation; Tumor Necrosis Factor-α